Pengaruh Senam Dismenorhea Terhadap Dismenore Pada Remaja - Yuliani, Istri; Verawati, Bernadeta; Wijayanti, Heny Noor; Sugathot, Aan Ika; Suhartati, Suhartati (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2023)
Dysmenorrhea or pain during menstruation is often experienced by women. Many adolescents experience dysmenorrhea in the first three years after menarche. Young adult women aged 17-24 years are the most likely to report painful menstruation. This study aims to determine the effect of disminorhea exercises on dysmenorrhea in adolescents in Selomartani Village, Kalasan, Sleman. This research was conducted with a quasi-experimental. Data measurements were taken before and after treatment. The sampling technique uses purposive sampling. The total sample was 7 respondents without a control group. Pain scale measurements were carried out before and after the dysmenorrhoea exercise procedure using the Numerical Rating Scale (NRS). Retrieval of data with a questionnaire, then analyzed with one group pre and post test. The results of the study obtained statistical test results with a p value of 0.018 where the p value <0.05. The results of this study is that there is an effect of dysmenorrhea gymnastics on dysmenorrhea in adolescents, so it is hoped that young women can do these exercises. By doing this exercise regularly, teenagers who experience dysmenorrhea will reduce the intensity of the pain and the incidence of dysmenorrhea will decrease.